The Trump Doctrine of Preemptive Extraterritorial Force: Targeted Killing Promises Against Nigerian Jihadists and the Crisis of International Legal Order - Nabiebu, Miebaka; Eja, Alobo Eni; Njong, Cleverty Afu; Agube, Ntamy (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
The January 2026 public declaration by the U.S. President Donald Trump vowing to order lethal strikes against Islamic State-affiliated jihadist factions in Nigeria represents a critical inflection point in the normative architecture governing the use of force. This paper conducts an extensive doctrinal and policy analysis of such a declaration, situating it within the broader “Trump Doctrine” of unilateral, preemptive military action that challenges the United Nations Charter’s foundational framework. The paper posits that promises of extraterritorial force against non-state actors (NSAs) in the territory of a consenting but weak sovereign state like Nigeria create a complex tripartite legal nexus involving: the jus ad bellum limits of self-defense against NSAs (the “unwilling or unable” test), the jus in bello principles of distinction, proportionality, and precaution in a counterterrorism context, and the emerging jus ad vim debate on the law of armed conflict short of war. Through a case study of Nigeria’s counterinsurgency against ISWAP and Boko Haram, analyzing the state’s capacity, territorial control, and ambiguous consent” the paper interrogates whether such U.S. action would constitute lawful collective self-defense, a violation of sovereignty, or an unlawful intervention. It further examines the dangerous precedent set by public, politically instrumental declarations of force, which risk eroding diplomatic channels, undermining host-state legitimacy, and legitimizing a global practice of “adversarial airstrike diplomacy.” The paper concludes that while the 2001 AUMF provides a contested domestic U.S. legal basis, the international legal permissibility hinges on a fact-specific assessment of Nigeria’s effective control and explicit consent, a threshold currently unmet in large parts of the Lake Chad Basin. Ultimately, the declaration epitomizes a trend toward the normalization of unilateral counterterrorism strikes, posing a systemic threat to the Article 2(4) prohibition and accelerating the fragmentation of international law into a hierarchy where powerful states dictate the rules of cross-border violence.